Relación entre la ecotextura del parénquima testicular y la producción y calidad seminal en toros de razas carniceras dadores de semen - Marcantonio, Sergio Ariel (2020)
Fertility is a key variable in bovine production. Although both sexes take part in the\npregnancy results, the quantitative relationship male:female means that the fertility of bulls plays a fundamental role. In the case of semen-donor bulls located in Semen\nCollection and Processing Centers (SCPC), the enormous capacity of artificial insemination for multiplying the reproductive potential makes the importance of male\nfertility even greater. A complete breeding soundness examination is a powerful tool for\nestimating the potential fertility of bulls. In the last twenty years, ultrasonography (US)\nhas begun to be considered a non-invasive, non-traumatic tool for evaluating the structure and function of the male reproductive tract. Computerized analysis of the ultrasound\nimage permits revelation of differences in echotexture that are imperceptible to the human eye and makes objective measurements possible. The objective of this study was to\nevaluate the potential of testicular US to predict the quali/quantitative capacity to produce semen in bulls belonging to SCPC. The work was carried out in the facilities of the CRB,\na SCPC located close to the town of San Antonio de Areco, in the province of Buenos Aires. A total of 57 semen-donor bulls, on a regular semen collection regime, were\nincluded in the study. Bulls were between 1.5 and 10 years of age and comprised the following beef-producing breeds: Angus, Brangus, Braford, Limangus and Polled Hereford. Semen collection was carried out using an artificial vagina. The number of\nejaculates processed and the production of frozen straws during the two weeks before and\nthe two weeks after the time ?0? (day of ultrasound), ?30? (30 days post ultrasound) and ?60? (60 days post ultrasound), were registered. Ultrasound images were taken using an\nEXAGO®\n ultrasound (ECM Angulemme, France) with a multifrequency linear\ntransducer configured at 7.5 MHz. Three transversal images were taken per testicle, in 3 positions: dorsal, medium and ventral. The images were analyzed using the ECOTEXT®\nsoftware. A correlation analysis was carried out between all the Ecotext variables (EC1=\nblack pixels, EC2= white pixels, EC3= mean gray level of pixels, Density= density of hypoechogenic areas, Diameter= mean diameter of hypoechogenic areas and Area\npercentage of hypoechogenic areas in the total area of the region of interets) and semen\nquality and production (time 0, time 30 and time 60). Then a bivariant and multivariant analysis (multinomial logistic regression) was carried out to predict the freezability of the ejaculates as related to breed, age or tubule density (density of hypoechogenic areas) measured by ultrasound. The distribution of the testicular echotexture and microstructure\nobtained in the semen-donor population of bulls were the following (mean ± S.D.):\nEC1:14.96 ± 10.76; EC2: 50.24 ± 105.58; EC3: 86.11 ± 11.83; Area: 11.86 ± 3.40;\nDiameter: 126.08 ± 23.73µm and Density: 137.54 ± 17.67. No significant differences\n(p>0.05) were observed between breeds or between ages for any of the ultrasound parameters considered. When analyzing the relationship between seminal quality and the\nparameters of testicular echotexture and microstructure at time 0, a positive relationship\nwas observed between the density of AH and seminal volume (r=0.32). In regard to sperm morphology, a highly significant negative relationship was observed between the\npercentage of abnormal heads and EC2, EC3 and tubule diameter (r= -0.37; -0.52; -0.37 respectively). Diameter was also negatively correlated with the percentage of other sperm morphological abnormalities (r= -0.30). The quantity of black pixels (EC1) was positively\ncorrelated with the area, density and diameter of the seminiferous tubules (r=0.69; 0.46\nand 0.53, respectively). No correlation was found between the Ecotext variables and\nseminal quality parameters at 30 days after the ultrasound measurements. A positive\ncorrelation was observed between area and diameter and sperm concentration in the\nejaculate 60 days after the ultrasound measurements (0.33 and 0.35, respectively). At day\n0, no correlation was observed between the Ecotext parameters and post-thaw motility.\nSignificant differences in area and diameter were observed between bulls that produced\ngood quality post-thaw ejaculates and those that produced ejaculates that were rejected at\n30 and 60 days post ultrasound. No differences were observed in the Ecotext parameters\nbetween bulls that produced 100 straws per ejaculate, 101 to 150 straws per ejaculate and\nmore than 150 straws per ejaculate. The AH density was the only Ecotext parameter that\npermitted a prediction of the freezing results on day 0. All bulls with up to 115 AH/cm2\nproduced semen that was not apt for freezing. In conclusion, despite having shown\ndifferent levels of association between the Ecotext parameters and semen quality, it\nremains necessary to continue the studies to be able to confirm the use of this tool to predict potential fertility of semen-donor bulls from CCPS.